Efficacy and Safety of Acupuncture for Cyclic Mastalgia: Study Protocol for a Randomized, Sham-Controlled Trial - Gao S; Sun Y; Shi H; Fang J; Liu Z (Dove Medical Press, 2023)
Shuai Gao,1,* Yuanjie Sun,1,* Hangyu Shi,1,2 Jiufei Fang,1 Zhishun Liu1 1Department of Acupuncture, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People's Republic of China; 2Graduate School, Beijing University of Chinese Medicine, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhishun Liu, Department of Acupuncture, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, No. 5 Beixiange Street, Xicheng District, Beijing, People's Republic of China, Email zhishunjournal@163.comPurpose: Cyclic mastalgia is prevalent among women and negatively impairs their daily life and work. There is still a lack of effective therapies for mastalgia, and acupuncture may be a promising method. We design this multicenter randomized trial to evaluate the efficacy and safety of acupuncture on cyclic mastalgia.Study Design and methods: Sixty participants with moderate-to-severe cyclic breast pain (with a duration of 5- 21 days and the worst pain scoring 5 points or more on Numerical Rating Scale [NRS]) will be recruited at three hospitals in China. They will be randomly assigned to acupuncture group or sham-acupuncture group at 1:1 ratio to receive 16-session treatment during 3 consecutive menstrual cycles, and follow-up for 6 menstrual cycles after treatment. The primary outcome is the change from baseline in the NRS score on the worst breast pain during the third cycle of treatment period. All statistical tests will be two-sided and P value < 0.05 will be considered statistically significant.Keywords: cyclic breast pain, complementary and alternative medicine, RCT, sham acupuncture